Food policy and the unruliness of consumption: An intergenerational social practice approach to uncover transforming food consumption in modernizing Hanoi, Vietnam - Wertheim-Heck, Sigrid C.O.; Raneri, Jessica Evelyn (Elsevier, 2020)
Globally, food policies strive to steer citizens in specific directions, however consumption remains largely unruly. This is also the case in Hanoi, Vietnam, where the food safety driven supermarketisation policy is only minimally successful in diverting consumers from traditional markets. Previous research demonstrated that low-income urbanites do not shop at supermarkets and maintain their minimally adequate diet quality through market shopping. Nevertheless, shifts in diets are occurring. The traditional local plant-based diet, which may be considered a ‘planetary health diet’, is shifting towards an increased uptake of animal proteins, ultra-processed foods and sugar sweetened beverages. This begs the question of how dietary shifts are shaping up. This paper aims to uncover emerging dietary trends by understanding the more hidden dynamics of food consumption in the everyday life of low-income urbanites. We use an intergenerational social practice approach to household food security, focussing on food access and utilization in balancing diet quality and food safety priorities within the context of Hanoi's changing food retail environment. Our qualitative methods, consisting of multi-generation household interviews and shopping trips, uncovered: (i) younger women prefer traditional food acquisition and preparation practices for modern convenience; (ii) the changing food environment is mitigated by informal relations and networks that are increasingly online; and (iii) fast-food is entering the home through pester power. Our results demonstrate food security is a dynamic interplay of food environments, food acquisition and preparation preferences, and creative agency, wherein food security takes different forms within changing contexts. We discuss the usefulness of our approach and recommend policy makers consult with populations directly impacted by planned food policies to ensure they are relevant and leverage the creative agency demonstrated by this population.